Clinical Outcomes for Hemiarthroplasty Versus Total Hip Arthroplasty in Patients With Femoral Neck Fracture Who Meet Published National Criteria for Total Hip Arthroplasty. Issue 1 (January 2022) - Craig, Julie; McDonald, Jonathon; Cassidy, Roslyn; McDonald, Sinead; Barr, John; Diamond, Owen
Abstract : Objectives: To examine outcome for patients with hip fracture treated by a hemiarthroplasty (HA) but who actually met the United Kingdom, National Institute for Health and Care Excellence (NICE) criteria for receiving a total hip arthroplasty (THA). Design: Match cohort study. Setting: Level 1, Academic Trauma Centre (UK Major Trauma Centre). Patients/Participants: Three hundred ninety-eight patients underwent either a HA or THA for a nonpathological displaced intracapsular fractured neck of the femur [OTA/AO 31 B3 (garden 3–4)], having met the NICE criteria for THA. Intervention: HA versus THA. Two analyses were performed, the first comparing the outcome in a cohort of patients who either received a THA or HA but who all had met the NICE criteria to receive a THA (n = 398). The second analysis assessed the outcome of THA versus HA, in a matched cohort of patients who all met the NICE criteria for a THA (n = 44 matched pairs). All patients in the matched cohort were able to walk independently outdoors (WIOs) before injury. Main Outcome: Mobility and functional outcome, 1 year after surgery. Results: Of the 398 patients who met the criteria for THA, only 78 (19.6%) patients actually received a THA. Within the matched cohort, significantly more THA patients (92.9%, 39/42) maintained the ability to WIOs at 1-year compared with patients with HA (56.4%, 22/39; P = 0.001). There was no difference in mortality, reoperation, or complication rates for our matched population at 1 year. Conclusions: Patients who meet the NICE criteria for THA and are able to WIOs preinjury are more likely to have a higher level of independent mobility and a better functional outcome at 1-year if they receive a THA, as opposed to receiving a HA. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.